DO CRISES INDUCE REFORM? A CRITICAL REVIEW OF CONCEPTION, METHODOLOGY AND EMPIRICAL EVIDENCE OF THE 'CRISIS HYPOTHESIS'. (22nd May 2017) - Mahmalat, Mounir; Curran, Declan
Abstract: The notion that economic crises induce the adoption of reform ranks among the most widely accepted concepts in the political economics literature. However, the underlying mechanism of the so‐called 'crisis hypothesis' has yet to be fully understood. This paper provides a comprehensive survey of the relevant empirical evidence to date, and scrutinizes the operationalization of the hypothesis' key concepts: crisis, reform and the political mediation of reform during crises. We argue that the social perception of both crises and the subsequent cost of reform requires consideration of how these concepts are operationalized. As a product of the broader economic and institutional environment, social perceptions largely determine the manner in which the political mediation of reform during crises works. Present‐day methodological approaches fail to adequately reflect social perceptions and consequently compromise the determination of what constitutes both crisis and the cost of reform in the context of the crisis hypothesis. Most notably, the identification of crises by fixed thresholds constructed around macroeconomic variables impedes the interpretation of the hypothesis' underlying mechanism. A fuller treatment of social perception within the operationalization of the hypothesis' key concepts can enhance our understanding of how economic crises influence political dynamics in bringing about reform.